Implementasi Kebijakan Restorative Justice Dalam Penegakan Hukum Tindak Pidana Penyalahgunaan Narkoba Di Kec. Alam Barajo Kota Jambi - Hariyanto; Bahrul Ulum; Ramlah (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This study aims to examine the law enforcement of criminal acts in Indonesia, as a country law , of course enforcement law that doesn't take sides has set in Constitution 1945 Constitution Article 27 paragraph (1) of the 1945 Constitution where everyone is treated same in front law . Restorative justice is an alternative law enforcement approach that prioritizes solidarity, custom and culture, as regulated in the decision letter of the Supreme Court of the Republic of Indonesia concerning application of restorative justice . Study this is a qualitative research using approach juridical empirical. Approach juridical (law) seen as norm or das sollen, because in discuss problem study this use materials law (good written law _ nor law that doesn't written, as well as applying the theory of criminal politics (criminal law application, prepention without punishment, influencing views of society on crime and punishment) However , on practice principle justice this not yet perfect applied on system law in Indonesia. Enforcement process law in Indonesia is still just there is element discrimination or privilege on party certain in handling case. This study resulted in four things, namely: Forms of restorative justice on drug abuse, MUI decree against eating and drinking containing alcohol /ethanol. The conclusion of the study is that drug abuse is a victim of crime, drug law enforcement can only be carried out with prevention without punishment and rehabilitation methods which are the implementation of restorative justice, drugs can be interpreted as khomar and the law is haram.